1991
DOI: 10.1111/j.1600-0722.1991.tb01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride release and uptake by glass ionomers

Abstract: Forsten L: Fluoride release and uptake by glass ionomers. ScandJ Dent Res 1991; 99: 241-5.Abstract -The aim was to study the fiuoride release 1) from 7 and 15-month-old glass ionomer specimens after treating them wilh fluoride; 2) from fresh compared with matured material; and 3) from specimens stored for 29 months in running water. Glass ionomer test specimens which had been in running water for first 7 then 15 months were treated with a 50 ppm fluoride solution after which the specimens were again exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 4 publications
7
77
0
14
Order By: Relevance
“…23 To compare the present data with the results from other papers [24][25][26][27][28] involving a similar range of materials, the same unit (ppm) was chosen for comparison and discussion. The treatment of data by Rothwell et al 29 using mg/g for fluoride release versus the square root of time, assumes that fluoride release will be completely exhausted at infinity, and has gradually gained acceptance for recent publications of fluoride release.…”
Section: Researchmentioning
confidence: 67%
“…23 To compare the present data with the results from other papers [24][25][26][27][28] involving a similar range of materials, the same unit (ppm) was chosen for comparison and discussion. The treatment of data by Rothwell et al 29 using mg/g for fluoride release versus the square root of time, assumes that fluoride release will be completely exhausted at infinity, and has gradually gained acceptance for recent publications of fluoride release.…”
Section: Researchmentioning
confidence: 67%
“…Thus, glass ionomer cement acts as a rechargeable device for fluoride release [7]. This capability has already been demonstrated by previous studies indicating that the regular use of toothpaste may result in the absorption of fluoride into the glass ionomer cement and subsequent release to the tooth structure [8,9].…”
Section: Introductionmentioning
confidence: 68%
“…[10][11][12][13][14] These materials will bond to enamel and dentine and leach fluoride. 15 The strongly radiopaque, silvercontaining, glass ionomers 16 have become popular although it is suggested that the occlusal access cavity should be sealed with composite resin to prevent wear of the underlying glass ionomer. 10,12 The efficacy of caries removal is perhaps a cause for concern bearing in mind the limited access afforded by the preparation.…”
Section: The Development Of the Tunnel Restorationmentioning
confidence: 99%